ANALYSIS OF KNOWLEDGE ABOUT FLOUR FOR READINESS OF PASTRY PRACTICE OF STUDENTS STUDY PROGRAM DIII HOSPITALITY HARAPAN BERSAMA POLYTECHNIC IN TEGAL - Anggraeni, Puput Dewi; Sabrina, Tantri Adithia (Journal of Indonesian Tourism and Policy Studies, 2020)
Students of DIII Hospitality Harapan Bersama Polytechnic inTegal are equipped with a number of productive courses, one of which is the Pastry course, where this course learns from the preparation, manufacturing, serving to storage of bread and cake with standard recipe specifications and company practices. But the knowledge of some students is still very low in the material "Flour" so it is feared that it will affect the readiness in the implementation of pastry practices. The purpose of this study was to determine the level of student knowledge related to the understanding of flour, types of flour, flour function, how to store flour, and use of flour in the material "Flour" for the readiness of pastry practice. The research method use descriptive methods with descriptive statistical analysis. The population is the Hospitality Study Program DIII students, amounting to 35 people. The instrument used in this study is a multiple choice objective test. The results of this study indicate that the level of student knowledge regarding flour material related to understanding, type, function and method of storing flour is quite good criteria and the level of student knowledge regarding flour material related to the use of flour in making pastry products is in good criteria. Suggestions submitted by researchers for pastry lecturers in order to continue to improve students' knowledge competence in flour material by giving assignments in the form of papers on flour material that is still poorly understood.